Penggunaan Laboratorium Virtual Materi Laju Reaksi untuk Meningkatkan Hasil Belajar Siswa SMAN 3 Muaro Jambi - Minarni Minarni; Epinur Epinur; Yusnidar Yusnidar; Wilda Syahri; Rusdi Rusdi; Afrida Afrida (JPM: Jurnal Pengabdian Masyarakat, 2023)
Reaction rate material is one of the materials from the Chemistry eye in high school which studies the concept of reaction rate, the factors that affect the reaction rate and purchase order of the reaction. In learning the goal is to say that mastery of concepts by students is through experiments/practicums, the same is the case with acid-base materials and other chemical materials. To realize the demands of the learning objectives of the reaction rate, practicum is needed. The purpose of community service is due to the limited tools and materials in the laboratory, so that the chemical practicum, especially the reaction rate, is not carried out. The ability of teachers in the field of ICT is very low, so teachers cannot operate and create virtual laboratories.